Simulai Pengaruh Nilai Kalor Pencampuran Batubara dan Beban Terhadap Kinerja Pembangkit Termal Studi Kasus PLTU di Suralaya - Prayudi Suparmin; Hendri MT (JURNAL POWERPLANT, 2019)
The performance of a boiler determined by the quality of coal as its fuel, influenced by its calorific value, moisture content, ash content, nitrogen, and carbon. To be use according the boiler specifications, the plant blends coal to get the heating value according to specifications. This study simulates the effect of mixing the coal heat value and load on the boiler performance The coal used is MRC a heating value of 5041 kcal and LRC a heating value 4920 kcal, with a blending ratio of 10:90; 20: 80; 30:70; 40:60 and 50:50. The coal blending used method the Canterper approach, and the boiler efficiency uses standard the ASME PTC 4-1. The results research, that most optimal mixing a ratio of 40: 60 and 50: 50, a calorific value of 4999 kcal/kg. The efficiency boiler increase in proportion to the increase in the calorific value. The boiler efficiency highest at ratio mixture of 50:50. The boiler efficiency highest is 85.94% and minimum is 85.25%. Value characteristics specific coal consumption to decrease proportionally to increase calorific value, the value lowest specific consumption at a mixture ratio of 50:50. The value SFC lowest is 0.465 kg/kWh and the highest is 0.479 kg / kWh. The value calorie higher, the lower the amount of specific coal consumption